2021
DOI: 10.3390/antiox10111679
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wine and Tyrosol on the Lipid Metabolic Profile of Subjects at Risk of Cardiovascular Disease: Potential Cardioprotective Role of Ceramides

Abstract: Ceramides are a class of sphingolipids which have recently been shown to be better cardiovascular disease (CVD) risk predictors than traditional CVD risk biomarkers. Tyrosol (TYR) is a dietary phenolic compound known to possess cardioprotective effects per se or through its in vivo active metabolite hydroxytyrosol. The purpose of this study was to evaluate the effects of the co-administration of white wine (WW) and TYR on circulating levels of ceramides and other lipids in humans at high CVD risk. Volunteers u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Importantly, both pharmacological (e.g., statins) and life-style intervention (diet, aerobic exercise) may modulate ceramide profile [ 1 , 56 , 57 , 58 ]. Interestingly, co-administration of tyrosol (a dietary phenolic compound) and white wine decreased levels of three ceramide ratios (Cer C16:0/Cer C24:0, Cer C18:0/Cer C24:0, and Cer C24:1/Cer C24:0) in parallel to improved endothelial function (assessed by augmentation index, an indirect measure of arterial stiffness, traditional lipids, D-dimer, homocysteine, C-reactive protein), in subjects at high cardiovascular disease risk [ 59 ].…”
Section: Ceramides and Cardiometabolic Riskmentioning
confidence: 99%
“…Importantly, both pharmacological (e.g., statins) and life-style intervention (diet, aerobic exercise) may modulate ceramide profile [ 1 , 56 , 57 , 58 ]. Interestingly, co-administration of tyrosol (a dietary phenolic compound) and white wine decreased levels of three ceramide ratios (Cer C16:0/Cer C24:0, Cer C18:0/Cer C24:0, and Cer C24:1/Cer C24:0) in parallel to improved endothelial function (assessed by augmentation index, an indirect measure of arterial stiffness, traditional lipids, D-dimer, homocysteine, C-reactive protein), in subjects at high cardiovascular disease risk [ 59 ].…”
Section: Ceramides and Cardiometabolic Riskmentioning
confidence: 99%
“…Another study investigated the impact of phenolic tyrosol supplementation on circulating levels of ceramides and other lipids in humans at high CVD risk. Diet containing white wine and tyrosol resulted in lower levels of three ceramide ratios, Cer (16 : 0)/Cer(24 : 0), Cer(18 : 0)/Cer(24 : 0), and Cer (24 : 1)/Cer(24 : 0), which associated with an improvement of endothelial function while also minimizing the alterations in plasma diacylglycerol concentrations observed following white wine, suggesting potential beneficial effects [27].…”
Section: Key Pointsmentioning
confidence: 93%
“…Higher levels of circulating ceramides were closely correlated with elevations of inflammatory cytokines, such as monocyte chemoattractant protein-1 (MCP-1) [ 15 ]. Moreover, ceramides have been a novel element in the regulation of coagulation [ 16 , 17 ], and the changes in ceramides were associated with altered blood coagulation function among participants with high risk of cardiovascular diseases [ 18 ]. To date, several studies have suggested that ceramides may play an important role in air pollution-associated atherosclerotic progressions, but evidence in humans is limited [ 19 ].…”
Section: Introductionmentioning
confidence: 99%